Daya Tarik Wisata Budaya Festival Peh Cun Dalam Meningkatkan Kunjungan Wisatawan di Kota Tangerang - Berutu, Feronika; Dhanka, Randy (Jurnal Ilmiah Global Education, 2024)
Every year the Peh Cun tradition is carried out to commemorate and pay tribute to the ancestors, this is also done by the Chinese community in Tangerang City. The Peh Cun festival contains a wide range of activities and traditions, but at the moment it is not much to implement. There needs to be an effort to preserve the culture to become a cultural tourist attraction in the city of Tangerang. The method used in this research is qualitative descriptive which means to understand the phenomena of what the subject is experiencing by means of description in word form. Data used in primary and secondary research, with techniques of gathering interviews, observations and documentation studies with data analysis techniques used in the way data is obtained, collected and then described in interactive models with stages of data condensation, presentation and conclusion. The results in this study are concluding. In order to improve the visits of tourists that can be made for maximum results, it is necessary to collaborate between Chinese and Betawi cultures, to cooperate with BUMN, private and educational institutions as well as collaborate with influencers in marketing, development and full support for the implementation of the Peh Cun Festival in the Cisadane River in the city of Tangerang. Such efforts are expected to enhance the visit with the appeal of beauty, uniqueness and value.